2006
DOI: 10.1177/0143831x06061072
|View full text |Cite
|
Sign up to set email alerts
|

The Working Conditions and Health of Non-Permanent Employees: Are There Differences between Private and Public Labour Markets?

Abstract: Increasing levels of non-permanent employment have raised concern about quality of working life in the public sector. This Finnish study examines whether the public sector can be characterized as a ‘model employer’ with regard to the working conditions and well-being of fixed-term employees. Compared to the private sector, the difference in the physical load between non-permanent and permanent employees is significantly smaller in the public sector. Comparison of psychosocial strain shows a difference in favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
13
2
Order By: Relevance
“…Previous studies have indicated that temporary employment is linked to higher psychological morbidity (77)(78)(79), and one may surmise that temporary employees may experience certain types of change as more threatening than permanent employees. Furthermore, employees working in temporary positions in private companies have been reported to experience a higher physical workload than their publicly employed counterparts (80). Hence, effects in the current study could be underestimated due to the large proportion of respondents with a presumably relatively secure work situation.…”
Section: Methodological Considerationsmentioning
confidence: 65%
“…Previous studies have indicated that temporary employment is linked to higher psychological morbidity (77)(78)(79), and one may surmise that temporary employees may experience certain types of change as more threatening than permanent employees. Furthermore, employees working in temporary positions in private companies have been reported to experience a higher physical workload than their publicly employed counterparts (80). Hence, effects in the current study could be underestimated due to the large proportion of respondents with a presumably relatively secure work situation.…”
Section: Methodological Considerationsmentioning
confidence: 65%
“…Although Saloniemi et al . (2004) and Virtanen et al . (2006) find that short‐term workers have better psychosocial work environments than permanent workers, Ferrie et al .…”
Section: Precarity Health and Workplace Absencementioning
confidence: 99%
“…The nature of temporary work is also found to have effects on psychological well-being both at and away from the workplace. Although Saloniemi et al (2004) and Virtanen et al (2006) find that short-term workers have better psychosocial work environments than permanent workers, Ferrie et al (1995) find that short-term workers have poorer mental health, perhaps linked to their fear of job loss (Cappelli, 1999). Furthermore, Kivimäki et al (2003) note a higher mortality rate as a result of tobacco or alcohol misuse among temporary workers.…”
Section: Precarity Health and Workplace Absencementioning
confidence: 99%
“…There is also a study among the personnel of a Finnish hospital district showing that temporary employees experience less exhaustion than do permanent employees (25). Moreover, a study based on a random sample of Finland's working aged population found in a cross-sectional setting and with the total core-periphery range of non-permanent employment that there is a health gradient, but this is located between temporary and the more atypical employment contracts, such as on-call or agency work, rather than between permanent and temporary employees (15), independently of the sector (public or private) of the labor market (26). Indications of a similar difference between more and less atypical employment have also been reported in a Swedish study (27) that differentiated five types of non-permanent employment according to the position on the core-periphery axis (28) and followed up a population cohort for 12 years.…”
Section: Discussionmentioning
confidence: 99%